Hospital STI prevention scheme adapted to target undiagnosed LGBT migrants in Paris area since 2018. (30th September 2020) - Bouchet-Mayer, C; Segouin, C; Kouadio-Sankadio, C P; Sow, A; Ramirez-Diaz, W; Ferez, S; Shelly, M
Abstract: Background: In Île-de-France region, 10 000 people do not know they are living with HIV (Supervie, 2016). 70% are men, including 40% men having sex with other men (MSM) and 40% sub-Saharan African migrants. From 35% to 49% of those sub-Saharan African migrants are infected in France. The main HIV prevention issues is to target populations that are unrepresented in screening test centers. Methods: To achieve these aims, a sexual health promotion scheme has been designed by a public health association, a Sexual Transmitted Infections (STI) center and an association supporting people asking asylum because of their "sexual orientation or gender identity". Outreach STI screening test actions are organized monthly in places crowded by asylum seekers and associative sexual health consultation including screening, results reporting, treatments, vaccinations and Pre-Exposition Prophylaxis (PrEP), devoted to asylum seekers are taking place weekly into the hospital. Pear community members have been trained to be referent in health matters and enhance the scheme effectiveness. Results: 549 people were screened for STI through 110 actions from March 2018 to December 2019, of which 25 were outreach and 85 inside the hospital. 74% were from sub-Saharan Africa and 86% were presumed MSM. 89% were under 40 years old. 20% of the screened people were diagnosed positive to at least one STI and 52 people have been engaged in PrEP treatment after a risky assessment. Pear referent involvement reduced the number of unreported results, 10% are still unreported. 21 people have stopped PrEP follow-up. Around 3/4 of those followed by the association on the period stand unreached. Conclusions: The scheme allowed to targeted population according to epidemiology's indicators but we don't know if the most exposed part of the population is reached. Partnership between associations and hospital improved public health system as well as community involvement. Key messages: Public health system needs adaptations to struggles epidemics. Community involvement must be a priority to increase prevention's efficiency .